Changes in the Level of Depressivity in Self-Harming Adolescents After the First Wave of the COVID-19 Pandemic (European Journal of Behavioral Sciences, 2021)
The COVID-19 pandemic and its consequences have not only had a somatic effect but has also had a psychological effect. Apart from various studies that point to the negative effects of the pandemic on the population´s mental health, there are also those that have dealt with its positive impact and have identified possible protective factors whose intensity have increased during the pandemic. The presented study focuses on the level of depressivity in a sample of self-harming adolescents through a comparison of its prevalence before and after the first wave of COVID-19. The results imply that the changes and measures brought by the first wave of the pandemic did not increase the prevalence of depressivity. The discussion presents the limitations of the research and the possible protective effects of a non-pathological home environment on the mental health of adolescents at risk.